Presence of p53 Mutations in 3Y1‐B Clone 1‐6: A Rat Cell Line Widely Used as a Normal Immortalized Fibroblast - Ushijima, Toshikazu (Jpn J Cancer Res, 1994)
The 3Y1 cell line, established from a rat whole embryo, is widely used as a normal immortalized fibroblast. We analyzed p53 mutations in four clonal lines derived from the 3Y1 cell line; 3Y1‐B clone 1–6, 3Y1‐C and two clonal lines (3Y1 cl‐3 and 3Y1 cl‐6) which had been transformed by the human papilloma virus E6 gene. Polymerase chain reaction (PCR)‐single strand conformation polymorphism (SSCP) analysis and DNA sequencing showed that three clonal lines had a double mutation at codons 130 and 136 on the same allele and that the other clonal line, 3Y1 cl‐3, had no mutations. 3Y1‐B clone 1–6, which has been registered as the standard clonal line at the Japanese Cancer Research Resources Bank, demonstrated weak bands of the wild type allele, suggesting the existence of heterogeneous cell types in this “clonal” line. PCR‐SSCP analysis of 25 subclones obtained by limiting dilution of 3Y1‐B clone 1–6 cells revealed a mixture of two types of cells; 12 subclones showed only the bands of mutated allele, and 13 subclones showed both bands of the wild and mutated p53 alleles. These findings should be taken into consideration when using this cell line as a normal immortalized cell line.